Statistical Analysis of the Acceleration of Baltic Mean Sea-Level Rise, 1900–2012 - Hünicke, Birgit; Zorita, Eduardo (Frontiers in Marine Science, 2016)
We analyse annual mean sea-level records from tide-gauges located in the Baltic and parts of the North Sea with the aim of detecting an acceleration of sea-level rise over the 20th and 21st centuries. The acceleration is estimated as a (1) fit to a polynomial of order two in time, (2) a long-term linear increase in the rates computed over gliding overlapping decadal time segments, and (3) a long-term increase of the annual increments of sea level. The estimation methods (1) and (2) prove to be more powerful in detecting acceleration when tested with sea-level records produced in global climate model simulations. These methods applied to the Baltic-Sea tide-gauges are, however, not powerful enough to detect a significant acceleration in most of individual records, although most estimated accelerations are positive. This lack of detection of statistically significant acceleration at the individual tide-gauge level can be due to the high-level of local noise and not necessarily to the absence of acceleration. The estimated accelerations tend to be stronger in the north and east of the Baltic Sea. Two hypothesis to explain this spatial pattern have been explored. One is that this pattern reflects the slow-down of the Glacial Isostatic Adjustment. However, a simple estimation of this effect suggests that this slow-down cannot explain the estimated acceleration. The second hypothesis is related to the diminishing sea-ice cover over the 20th century. The melting o of less saline and colder sea-ice can lead to changes in sea-level. Also, the melting of sea-ice can reduce the number of missing values in the tide-gauge records in winter, potentially influencing the estimated trends and acceleration of seasonal mean sea-level This hypothesis cannot be ascertained either since the spatial pattern of acceleration computed for winter and summer separately are very similar. The all-station-average-record displays an almost statistically significant acceleration. The very recent decadal rates of sea-level rise are high in the context of the 20th and 21st centuries, but they are not the highest rates observed over this period.